Tinjauan Yuridis-Sosiologis Pada Perkawinan Berbeda Agama Dalam HAM Dan Hukum Di Indonesia Serta Kedudukan pada Anak dari Perkawinan Berbeda Agama - Mutiara Mega Putri Utami; Taun Taun (Peneliti.net, 2023)
Indonesia consists of a diversity of ethnicities, races, cultures and beliefs. One of the most basic pluralisms of the Indonesian nation is the pluralism of beliefs held by the nation. In Indonesia, there are six recognized religions, each of which has its own rules. Like the rules of marriage. In Indonesia there are 2 marriage registration institutions, namely in Islam it is registered at the Office KUA while non-Muslims are registered at the Civil Registry Office (KCS). In KUA itself, interfaith marriages cannot be recorded, as well as in Disdukcapil unless there is a provision for dispensation. Indonesia needs regulations regarding religious marriages, so that there is no legal vacuum in this matter, especially since Indonesia is a pluralistic country where there are many different beliefs. So that there is no more debate in interfaith marriages.